2020
DOI: 10.1021/acs.jpcc.0c03487
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photophysical Properties of Bi2S3/AgBiS2 Nanoheterostructures Synthesized via Ag(I) Cation Exchange-Mediated Transformation of Binary Bi2S3

Abstract: Nanoheterostructures with multiple components and interfaces have gained much attention due to their promising photophysical properties. Here, we have synthesized rod-shaped Bi 2 S 3 /AgBiS 2 heterostructures via a cation exchange reaction, starting from the binary parent compound Bi 2 S 3 . The effective ionic radius of monovalent Ag + ion is proved to be the key factor for the intercalation of Ag + ions into the consecutive layers of the orthorhombic Bi 2 S 3 (212) plane and finally for the total conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Bismuth‐based materials are significantly attractive due to their broad NIR absorption, in vivo and in vitro photothermal effect, and low cost [1,6] . Specifically, AgBiS 2 is known for various applications [1,3,6,9–21] and most prominently as good photothermal agents as they are non‐toxic, in vivo, and in vitro biocompatible [1,6] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bismuth‐based materials are significantly attractive due to their broad NIR absorption, in vivo and in vitro photothermal effect, and low cost [1,6] . Specifically, AgBiS 2 is known for various applications [1,3,6,9–21] and most prominently as good photothermal agents as they are non‐toxic, in vivo, and in vitro biocompatible [1,6] …”
Section: Introductionmentioning
confidence: 99%
“…[5] Bismuth-based materials are significantly attractive due to their broad NIR absorption, in vivo and in vitro photothermal effect, and low cost. [1,6] Specifically, AgBiS 2 is known for various applications [1,3,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] and most prominently as good photothermal agents as they are non-toxic, in vivo, and in vitro biocompatible. [1,6] Many methods are available to synthesize AgBiS 2 nanoparticles, including microwave, solvothermal, and solid-state chemical reaction methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AgBiS 2 exists in two structural phases namely β-AgBiS 2 belongs to hexagonal structure (low temperature phase) and α-AgBiS2 belongs to a cubic structure (high-temperature phase). The latter one is of interest because it has potential applications in different elds such as photovoltaics and thermoelectric devices etc [7][8][9][10]. For instance, ITO/ZnO/AgBiS 2 /PTB7/MoO/Ag devices fabricated by J. T. Oh et al, (2020) [11] and I.…”
Section: Introductionmentioning
confidence: 99%
“…Oberg et al, (2020) [13] fabricated ITO/ZnO/AgBiS 2 (CQDs)/P3HT/MoO 3 /Ag device which showed lower photocurrent density. S. Paul et al, (2020) [8] have synthesized rod-shaped Bi 2 S 3 /AgBiS 2 heterostructures via cation exchange reaction, starting from binary parent compound Bi 2 S 3 . AgBiS 2 photodetector has exhibited broadband response with decent detectivity, and fast response of 700 ns reported by L. Jiang et al, (2020) [14].…”
Section: Introductionmentioning
confidence: 99%